2007
DOI: 10.1212/01.wnl.0000271883.45010.8a
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, hypercholesterolemia, diabetes, and risk of Parkinson disease

Abstract: Results of this large prospective study suggest that Parkinson disease risk is not significantly related to history of hypertension, hypercholesterolemia, or diabetes but may modestly decline with increasing blood cholesterol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
199
4
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(226 citation statements)
references
References 38 publications
9
199
4
5
Order By: Relevance
“…The larger Nurses Health Study and Health Professionals Follow-up Study (in total 530 incident PD cases) found no association between self-reported high cholesterol and PD [634]. However, similar to the Rotterdam study [640], a trend of decreasing PD risk with increasing levels of self-reported total serum cholesterol was observed that was significant in women (p for trend 0.04) but not in men (p for trend 0.19) [634]. In contrast, a…”
Section: Vascular Diseasesmentioning
confidence: 91%
See 3 more Smart Citations
“…The larger Nurses Health Study and Health Professionals Follow-up Study (in total 530 incident PD cases) found no association between self-reported high cholesterol and PD [634]. However, similar to the Rotterdam study [640], a trend of decreasing PD risk with increasing levels of self-reported total serum cholesterol was observed that was significant in women (p for trend 0.04) but not in men (p for trend 0.19) [634]. In contrast, a…”
Section: Vascular Diseasesmentioning
confidence: 91%
“…Similarly, no association between hypertension and PD was observed in the larger (in total 530 cases) prospective Nurses Health Study and the Health Professionals Follow-up Study [634]. These authors observed a decline in systolic blood pressure following diagnosis of PD [634].…”
Section: Vascular Diseasesmentioning
confidence: 94%
See 2 more Smart Citations
“…However, the effect of age on hypertension in PD patients was significant when faced with evidence from the literature that hypercholesterolemia, arterial hypertension and diabetes do not show correlations with the risk of PD 6,7 . It should be noted that arterial hypertension, dyslipidemia and diabetes do not seem to be associated with occurrences of either PD or dementia throughout their evolution.…”
Section: Discussionmentioning
confidence: 99%